Role of Fungi in Biodegradation of Imidazolium Ionic Liquids by Activated Sewage Sludge - Joanna Klein; Justyna Łuczak; Anna Brillowska-Dąbrowska (Molecules, 2023)
Ionic liquids (ILs), due to their specific properties, can play the role of persistent water contaminants. Fungi manifest the ability to decompose hardy degradable compounds, showing potential in the biodegradation of ILs, which has been studied extensively on sewage sludge; however, attention was drawn mainly to bacterial and not fungal species. The aim of the research was to determine the significance of fungi in ILs’ biodegradation to extend the knowledge and possibly point out ways of increasing their role in this process. The research included: the isolation and genetic identification of fungal strains potentially capable of [OMIM][Cl], [BMIM][Cl], [OMIM][Tf2N], and [BMIM][Tf2N] degradation, adjustment of the ILs concentration for biodegradability test by MICs determination and choosing strains with the highest biological robustness; inoculum adaptation tests, and finally primary biodegradation by OECD 301F test. The study, conducted for 2 mM [OMIM][Cl] as a tested substance and consortium of microorganisms as inoculum, resulted in an average 64.93% biodegradation rate within a 28-day testing period. For the individual fungal strain (Candida tropicalis), the maximum of only 4.89% biodegradation rate was reached in 10 days, then inhibited. Insight into the role of fungi in the biodegradation of ILs was obtained, enabling the creation of a complex overview of ILs toxicity and the possibilities of its biological use. However, only an inoculum consisting of a consortium of microorganisms enriched with a selected strain of fungi was able to decompose the IL, in contrast to that consisting only of an individual fungal strain.